Long-chain fatty acid acylated derivatives of isoflavone glycosides from the rhizomes of Iris domestica. (January 2022) - Li, Jiayuan; Ni, Gang; Liu, Yanfei; Wang, Renzhong; Yu, Dequan
Abstract: Six undescribed long-chain fatty acid esters of isoflavone glycosides were obtained from the rhizomes of Iris domestica (L.). Their structures were elucidated by comprehensive spectroscopic data, alkaline hydrolysis, and acid hydrolysis. This is the first report of the long-chain (C14 –C18 ) fatty acid derivatives of isoflavone glycosides from natural products. Belamcandnoate B and D exhibited moderate cytotoxic activities against HCT-116, HepG2, and BGC823 cell lines with IC50 values of 1.69–6.86 μ M. Belamcandnoate B and E exhibited 72.27 and 58.98% inhibitory activities, respectively, against Fe 2+ /cysteine-induced liver microsomal lipid peroxidation at a concentration of 10 μ M. Graphical abstract: Six long-chain fatty acid acylated derivatives were obtained from the rhizomes of Iris domestica . Compounds 2 and 4 displayed moderated cytotoxic activities, and compounds 2 and 5 exhibited potential inhibitory activities against Fe2+/cysteine-induced liver microsomal lipid peroxidation. Image 1 Highlights: Six long-chain fatty acid esters of isoflavone glycosides were obtained from the rhizomes of Iris domestica L.. It is the first report of long-chain fatty acid ester derivatives of isoflavone glycosides from natural products. In vitro bioassay, the cytotoxic and anti-oxidant activities for the isolated compounds were evaluated.